2009
DOI: 10.1097/sap.0b013e318195bfdd
|View full text |Cite
|
Sign up to set email alerts
|

The Use of a Retroauricular Fascioperichondrial Flap in the Recreation of the Antihelical Fold in Prominent Ear Surgery

Abstract: The surgical treatments for prominent ears are on the basis of the approach over the basics of the deformity decrease the concha-mastoid angle and create a new antihelical fold. The author describes a new retroauricular flap to be used in the recreation of the antihelical fold and critically analyzes the cosmetic results and complications. A skin ellipse is outlined on the posterior surface of the ear. After hydrodissection with anesthetic solution in the outlined area, the skin is removed as thin as possible … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
4
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 32 publications
1
4
0
Order By: Relevance
“…Frascino described the use of a postauricular fascioperichondrial flap with Furnas conchomastoid sutures that can be used with or without Mustarde sutures. 14 Additionally, Cihandide et al reported a distal perichondro-adipo-dermal flap, which is similar in composition to the flap described in the present study. However, a significant difference is that Cihandide et al advocate for the use of the flap without Mustarde sutures, as they believe that the continuity of the flap as opposed to discrete sutures provides improved antihelical creation in the attempt to decrease suture extrusion and recurrence rates.…”
Section: Discussionsupporting
confidence: 81%
“…Frascino described the use of a postauricular fascioperichondrial flap with Furnas conchomastoid sutures that can be used with or without Mustarde sutures. 14 Additionally, Cihandide et al reported a distal perichondro-adipo-dermal flap, which is similar in composition to the flap described in the present study. However, a significant difference is that Cihandide et al advocate for the use of the flap without Mustarde sutures, as they believe that the continuity of the flap as opposed to discrete sutures provides improved antihelical creation in the attempt to decrease suture extrusion and recurrence rates.…”
Section: Discussionsupporting
confidence: 81%
“…The ratio of unilateral cases to bilateral cases operated on at our center is higher than cases reported in Western articles. In Salgarelli et al's article,8 unilateral cases were 5% among 140 operated cases, and in Frascino's article,15 unilateral cases were about 4% among 82 operated cases. In the East, bilateral prominent ears have been the accepted tradition,17 and operations on bilateral cases are fewer than those of unilateral cases.…”
Section: Discussionmentioning
confidence: 93%
“…The postauricular fascial flap technique is relatively simple 15. Even though we used it as an adjuvant procedure, we encountered difficulty during flap dissection.…”
Section: Discussionmentioning
confidence: 99%
“…Another important advantage of the fascial flap technique that may reduce recurrences is that it forms an additional barrier that may prevent the suturing materials from being exposed. 16,17 However, all the techniques described for the suture-assisted otoplasty work either in children or in the existence of a pliable cartilage. 18 Although the scoring performed on the anterior surface of the cartilage to form an antihelical fold was described by Davis and Gibson in 1958 (discussed in Bhatti and Donovan 19 ), it was popularized by Stenstrom 20 and Chongchet.…”
Section: Discussionmentioning
confidence: 99%